2007
DOI: 10.1007/s12032-007-9011-5
|View full text |Cite
|
Sign up to set email alerts
|

Thirty patients with primary plasma cell leukemia: a single center experience

Abstract: The primary plasma cell leukemia (PCL) is a rare aggressive plasma cell dyscrasia. We investigated its clinical and laboratory aspects in a large series of patients. Among 934 consecutive patients with multiple myeloma (MM), registered between 1978 and 2004 in a single institution, 30 patients [M/F: 22/8; median age (yr): 60, range: 36-79] with PCL (3.1%) were diagnosed. Retrospective analysis of the clinical, immunophenotypic, and cytogenetic aspects was performed. All patients had anemia, thrombocytopenia, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 17 publications
3
38
1
3
Order By: Relevance
“…Recent attempts at genetic and molecular profiling of PCL have shown cytogenetic abnormalities in over 70% of PCL patients [10]. Hypodiploidy and complex karyotypes with multiple numerical and structural abnormalities involving chromosome 1, 13 and 14 are reported in a significant number of PCL cases [4,5,11] including report from India of multiple cytogenetic abnormality in a case of pPCL [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent attempts at genetic and molecular profiling of PCL have shown cytogenetic abnormalities in over 70% of PCL patients [10]. Hypodiploidy and complex karyotypes with multiple numerical and structural abnormalities involving chromosome 1, 13 and 14 are reported in a significant number of PCL cases [4,5,11] including report from India of multiple cytogenetic abnormality in a case of pPCL [12].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pPCL are younger; often have extra osseous organ involvement, with increased frequency of renal failure, fast declining performance status and rapid progression to the terminal stage. The liver, spleen and other extramedullary sites are more commonly involved than sPCL [11]. Compared to pPCL, patients with sPCL have advanced bone disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…Prior descriptive studies on pPCL have suggested a median overall survival (OS) of less than 12 months based on patients who did not receive novel agents. 1,[10][11][12][13] However, recent retrospective studies suggest that the incorporation of novel agents as well as ASCT in treating pPCL has improved the median OS to more than 24 months. [14][15][16][17][18][19] Given the lack of large, prospective studies evaluating the survival outcomes in pPCL because of its rarity, we used the Surveillance Epidemiology and End Results (SEER) program to evaluate the survival trends in pPCL patients in the US population during various time intervals based on the availability of ASCT and novel agent therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PCL have higher prevalence of hepatosplenomegaly, lymphadenopathy and thrombocytopenia. They also have a lower serum M protein level, extramedullary involvement, and frequently presents with renal failure [2,[9][10][11]. The surface phenotype of plasma cells in PCL is different from that of bone marrow plasma cells in patients with multiple myeloma: CD9, HLADR, CD117, and CD20 are differentially expressed in circulating plasma cells compared with bone marrow plasma cells in myeloma patients.…”
Section: Discussionmentioning
confidence: 99%